TINDAK TUTUR ILOKUSI DALAM NOVEL KETIKA CINTA BERTASBIH KARYA HABIBURAHMAN EL SHIRAZY - Hakim Prasasti Lubis; Lasmi Hartati; Tri Budiarti Damanik (Universitas Batanghari, 2026)
The issue of this research also focuses on illocutionary acts that can depict social changes and character development in the context of everyday life. As the plot develops in Ketika Cinta Bertasbih by Habiburrahman El Shirazy, we can see changes in the way the characters communicate, influenced by their circumstances, whether in terms of emotions, life decisions, or their relationships with religion and society. The aim is to identify and analyze the types of illocutionary acts used in the novel Ketika Cinta Bertasbih by Habiburrahman El Shirazy. This research uses a descriptive research method with a qualitative approach. The data collection methods used were the reading and note-taking methods. The results of this study on the meaning of illocutionary acts consist of: assertive illocutionary acts, directive illocutionary acts, expressive illocutionary acts, commissive illocutionary acts, and declarative illocutionary acts. The analysis of illocutionary acts serves as a guide for interpreting the meanings found in the dialogue of each character in the novel